Treatment of perianal abscess and anal fistula in infants: a systematic review - Chen, Jinlan; Xiong, Yi; Wang, Cong; Xu, Li (Frontiers in Surgery, 2025)
IntroductionThe optimal treatment approach for perianal abscess (PA) and fistula-in-ano (FIA) in infants remains a subject of debate.Material and MethodsA thorough literature search was conducted across multiple databases, including Embase, PubMed, Web of Science, Cochrane Library, ClinicalTrials.gov, and Google Scholar.ResultsA total of eighteen retrospective studies, encompassing 1,770 patients, were analyzed. Of the 702 cases (38.7%) that underwent conservative treatment, 528 cases (75.2%) achieved a cure, while 174 cases (24.8%) were unsuccessful, with 93 experiencing PA recurrence and 81 developing FIA. In contrast, among the 1,068 cases (61.3%) that received surgical interventions, 784 cases (73.4%) were cured, whereas 284 cases (26.6%) were not, with 151 experiencing PA recurrence and 133 developing FIA.ConclusionThe available studies indicate minimal differences in the cure and recurrence rates of PA and FIA between the conservative and surgical treatment groups.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/, PROSPERO (CRD42023472249).